Investment in soil conservation in northern Ethiopia: The role of land tenure security and public programs - Gebremedhin, Berhanu; Swinton, S.M. (Wiley, 2003)
A double hurdle statistical analysis of 250 farms in the Tigray region of Ethiopia reveals different causal factors for soil conservation adoption versus intensity of use. Farmers' reasons for adopting soil conservation measures vary sharply between stone terraces and soil bunds. Long-term investments in stone terraces were associated with secure land tenure, labour availability, proximity to the farmstead and learning opportunities via the existence of local food-for-work (FFW) projects. By contrast, short-term investments in soil bunds were strongly linked to insecure land tenure and the absence of local food-for-work projects. Public conservation campaigns on private plots reduced adoption of both stone terraces and soil bunds. Whereas capacity factors largely influenced the adoption decision, expected returns carried more influence for the intensity of stone terrace adoption (measured as metres of terrace per hectare). More stone terracing was built where fertile but erodible silty soils in higher rainfall areas offered valuable yield benefits. Intensity of terracing was also greater in remote villages where limited off-farm employment opportunities reduced construction costs. These results highlight the importance of the right kind of public interventions. Direct public involvement in constructing soil conservation structures on private lands appears to undermine incentives for private conservation investments. When done on public lands, however, public conservation activities may encourage private soil conservation by example. Secure land tenure rights clearly reinforce private incentives to make long-term investments in soil conservation